2009
DOI: 10.1016/j.jhazmat.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and co-precipitation behavior of arsenate, chromate, selenate and boric acid with synthetic allophane-like materials

Abstract: Pollution caused by boric acid and toxic anions such as As(V), Cr(VI) and Se(VI) is hazardous to human health and environment. The sorption characteristics of these environmentally significant ionic species on allophane-like nanoparticles was investigated in order to determine whether allophane can reduce their mobility in the subsurface environment at circum-neutral pH condition. Solutions containing 100 or 150 mmol of AlCl 3 . 6H 2 O were mixed to 100 mmol of Na 4 SiO 4 and the pH were adjusted to 6.4±0.3. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 33 publications
(46 reference statements)
6
31
0
4
Order By: Relevance
“…Furthermore, one can see that 5-10 min is enough to achieve adsorption equilibrium under the experimental conditions used in this study, which indicates that physical adsorption rather than ion exchange contributes mainly to the removal of metal ions by natural and synthetic allophane adsorbents. This finding is in line with previous experimental results, where allophane has been successfully used in the remediation of aqueous solutions that were contaminated with, for example, heavy metals cations [15,22,33,35], metal (oxy)anions [18,23,30], heterocyclic organic components [10] and anionic surfactants and organic acids [17,23]. …”
Section: Effect Of Contact Time On the Adsorption Kinetics Of Aqueoussupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, one can see that 5-10 min is enough to achieve adsorption equilibrium under the experimental conditions used in this study, which indicates that physical adsorption rather than ion exchange contributes mainly to the removal of metal ions by natural and synthetic allophane adsorbents. This finding is in line with previous experimental results, where allophane has been successfully used in the remediation of aqueous solutions that were contaminated with, for example, heavy metals cations [15,22,33,35], metal (oxy)anions [18,23,30], heterocyclic organic components [10] and anionic surfactants and organic acids [17,23]. …”
Section: Effect Of Contact Time On the Adsorption Kinetics Of Aqueoussupporting
confidence: 92%
“…In addition, gibbsite and quartz were identified in this sample, which matches with the XRD results. The main lattice vibration bands of the allophanes are located between 1000-980cm -1 and at 870 cm -1 due to Si-O-(Si) or Si-O-(Al) vibrations and Si-OH groups [19,30,31]. The IR spectra of SynAllo-1 and SynAllo-2 are similar to those reported for natural allophane, which shows that proto-imogolite allophane or imogolite structures did not form under the given experimental conditions [19,25,32].…”
Section: Mineralogical Characterization Of Allophane Adsorbentssupporting
confidence: 63%
See 2 more Smart Citations
“…Some researchers reported that As(V) and boric acid were adsorbed by formation of inner-sphere complex with exposed aluminol groups on the allophane surface while Cr(VI) and Se(VI) were adsorbed by formation of outersphere complex. 4,5) In this study, we have developed a synthesis process of allophane utilizing the undissolved residue of BFS by acid treatment. Identification of the synthesized allophane was performed by X-ray diffraction (XRD) for long range order, Fourier transform infrared (FT-IR) spectroscopy for short range order and transmission electron microscopy (TEM) for morphology.…”
Section: Introductionmentioning
confidence: 99%